Phytochemicals and Lipase Inhibition of Citronella, Galangal, and Sand Galangal: In Vitro–In Silico Approaches - Aghnia, Diya; Hasim, Hasim; Ambarsari, Laksmi; Faridah, Didah Nur; Slameut, Fitria; Kandi, Rizky Putra (Jurnal Teknologi dan Industri Pangan, 2025)
Obesity is a major global health concern, often treated by inhibiting pancreatic lipase to reduce fat absorption. While chemical-based medicine is a widely used synthetic inhibitor, its side effects highlight the need for safer, natural alternatives. This study aimed to characterize the total phenolic content (TPC), total flavonoid content (TFC), antioxidant activity, and pancreatic lipase inhibition of citronella leaf (Cymbopogon nardus), galangal rhizome (Alpinia galanga), and sand galangal rhizome (Kaempferia galanga) through in vitro and in silico analyses and to identify the potential phytochemical compounds responsible for the activity. Citronella showed the highest TPC, TFC, and FRAP values (14.20±0.21 mg GAE/g, 17.36±9.51 mg QE/g, and 92.01±1.88 µmol TE/g, respectively), indicating strong antioxidant potential. Galangal exhibited the highest extraction yield (21.86±5.34%) and DPPH activity (1.09±0.27 µmol TE/g). In vitro lipase inhibition assays revealed galangal and sand galangal had moderate inhibitory effects (IC50= 401.2±18.24 and 374±11.24 µg/mL), while citronella showed weak activity. LC-MS/MS analysis of galangal identified eight compounds, including galangin, eugenol, and galanganol C. Molecular docking showed galangin had the strongest binding affinity (ΔG= -10.239 kcal/mol), interacting with catalytic residues Ser152 and His263 of pancreatic lipase via hydrophobic and electrostatic interactions. These findings suggest that citronella, galangal, and sand galangal possess potential as natural pancreatic lipase inhibitors, with galangal particularly galangin showing the most promising activity for obesity prevention and management.